Study on the Effect of Water Pollution in Lubricant on Gear Thermal Elastohydrodynamic Lubrication Characteristic - Yan Chen; Xian Zhang; Guosheng Li (Jixie chuandong, 2021)
Taking the involute spur gear as the research object and considering the thermal effect and time-varying effect，the oil-water two-phase flow model and the thermal elastohydrodynamic lubrication model of the gear system are established，the influence of water content on the viscosity of the lubricants and the lubrication performance of the tooth surface are explored. The results show that when the water content in lubricating oil is less than 5%，the viscosity of oil-water two-phase fluid increased with the increment of water content. When the water content is 5%，the viscosity of oil-water two-phase fluid reached its peak value，and then decreased with the increment of water content. Appropriate increase of water content can improve the lubrication characteristics of tooth surface，but considering oil film temperature rise and corrosion wear of equipment，the water content should be controlled within 5%.